2015
DOI: 10.1021/jacs.5b02716
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Nanometer-Sized Boroxine Cages from Diboronic Acids

Abstract: By use of the reversible trimerization of boronic acids, the series of boroxine cages 3-mer, 6-mer, and 12-mer were constructed from rationally designed diboronic acids whose bond angles between two C-B bonds are 60°, 84°, and 117°, respectively. Boroxine cages 6-mer and 12-mer have 1.5 and 2.5 nm sized cavities, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 45 publications
2
72
0
7
Order By: Relevance
“…[3][4][5] In particular, reversible polymers, constructed around reversiblec ovalent or non-covalentb onds, are desirable because they enable intrinsic self-healing capabilities through their dynamic features. From this perspective, although the dynamic covalent nature of boroxine-ring formation has been commonly used in the design of covalent organic frameworks (COF) at its best, [23][24][25][26] in our case, we wanted to exploit this feature to achieve as elf-healing mechanism.As shown in Figure1,i minoboronate consists of as tructure in whicha ni mine interactst hrough its nitrogen-atom lone pair of electrons with an electron-deficient boron, located in the boroxine in our case. [6] Although much research data on this particularb ranch of chemistry hasb een reported, the majord rawback is the requirement for energy-demanding externala ctivations [7] to induce reversibility,s uch as temperature, [8][9][10][11] pH changes, [12] or light.…”
mentioning
confidence: 99%
“…[3][4][5] In particular, reversible polymers, constructed around reversiblec ovalent or non-covalentb onds, are desirable because they enable intrinsic self-healing capabilities through their dynamic features. From this perspective, although the dynamic covalent nature of boroxine-ring formation has been commonly used in the design of covalent organic frameworks (COF) at its best, [23][24][25][26] in our case, we wanted to exploit this feature to achieve as elf-healing mechanism.As shown in Figure1,i minoboronate consists of as tructure in whicha ni mine interactst hrough its nitrogen-atom lone pair of electrons with an electron-deficient boron, located in the boroxine in our case. [6] Although much research data on this particularb ranch of chemistry hasb een reported, the majord rawback is the requirement for energy-demanding externala ctivations [7] to induce reversibility,s uch as temperature, [8][9][10][11] pH changes, [12] or light.…”
mentioning
confidence: 99%
“…Dynamic covalent chemistry (DCC) is now employed widely in the construction of various nanostructures, including macrocycles, molecular cages, and other topologically significant structures,14–16 on account of the inherent proof‐reading and error‐correcting characteristics associated with these reversible reactions and the robustness of covalent bonding. The dynamic process of these nanostructures may have broad implications for the design and development of smart materials 17.…”
Section: Methodsmentioning
confidence: 99%
“…Über die ersten Synthesen von sphärischen Objekten wie Cuban [72] oder Carce-randen [73] wurde zwar schon vor einigen Jahrzehnten berichtet;d ie mehrstufigen Syntheserouten unter irreversibler Bindungsknüpfung waren jedoch durch sehr schlechte Ausbeuten und aufwändige Reinigungsschritte beeinträchtigt. Die beiden mit weitem Abstand am häufigsten eingesetzten Reaktionstypen fürd ie Synthese von COFs und Käfigen sind Boronatester- [75,76,80] (Schema 1) und Iminkondensationen [59,77,81] [83][84][85] als auch Boroxinkondensationen [86] wurden auch fürd ie Herstellung von kovalenten organischen Käfigen eingesetzt. Die Bildung von kovalenten, aber reversiblen Bindungen ist fürorganische Reaktionen wegen der üblicherweise recht großen Bindungsstärken nicht die Norm, kann aber trotzdem füre inige Kondensations-und Additionsreaktionen beobachtet werden.…”
Section: Dynamisch-kovalente Reaktionenunclassified
“…[85,86] Brønsted-Säuren wie AcOH [93][94][95] oder Metalltriflate als wasserverträgliche Lewis-Säuren [196] werden typischerweise zur Katalyse der Iminbildung eingesetzt. Sowohl die präzise Kontrolle der nanoskaligen Morphologie als auch verlässliche Vorschriften fürd ie Prozessierung der Materialien sind Schlüsselfaktoren fürd ie Entwicklung von zukünftigen Anwendungen dieser Strukturen.…”
Section: Synthese Und Prozessierungunclassified
See 1 more Smart Citation